Penampilan Vegetatif Tiga Genotipe Kedelai Berbiji Besar Pada Kondisi Stres Genangan - Kisman Kisman; Farid Hemon; Sumarjan Sumarjan; Suprayanti Dewi (LPPM Universitas Mataram, 2021)
ABSTRACTThis study aims to determine the vegetative appearance of three genotypes of large-seeded soybean under puddle stress. The Experimental method was used and the plastic buckets as the experimental units were arranged using a Split Plot Design. The main plot was the stress factor (S) consisting of normal conditions (S0) and puddle stress (S1), and the subplot was the genotype factor (G) consisting of G1 (KH1), G2 (Argomulyo), and G2 (Grobogan). Each genotype was repeated four times. The observed variables were plant height, number of leaves, leaf area, number of productive branches, specific leaf weight, root/shoot dry weight ratio. The results showed that there were significantly differences in the appearance of the vegetative characters of the three genotypes of large seeded soybean under puddle stress conditions, especially on plant height, leaf area, plant dry weight, and shoot dry weight. Under puddle stress conditions, KH1 showed the highest of the plant height, root dry weight, and shoot dry weight. Argomulyo showed the highest of the leaf area, while Grobogan did not show as a tolerant variety under puddle stress conditions.